2016
DOI: 10.18632/oncotarget.13774
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of immune regulatory cells with combined therapy of celecoxib and sunitinib in renal cell carcinoma

Abstract: ObjectiveTo observe the the potential benefit of sunitinib in combination with cyclooxygenase-2(COX-2) inhibitor in renal cell carcinoma therapy.Methods769-p cell lines were treated with sunitinib, celecoxib, or in combination at different concentrations respectively. We investigated the expression of granulocyte-macrophage colony stimulating factor (GM-CSF) in 769-p and cell proliferation in vitro. BALB/c mice implanted with Renca cells were divided into 4 groups and administered orally by gavage with sunitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…We observed temporal changes in these subpopulations over the course of the inflammatory response that indicate a close interaction with mesenchymal progenitor cells leading to aberrant healing. While immune modulating therapies have become a mainstay in cancer therapies, they have failed to translate to diseases of nononcogenic aberrant cell fate [36][37][38][39] . Here, we have validated a therapeutic approach that modulates the macrophage phenotype to prevent aberrant musculoskeletal regeneration in a model of HO.…”
Section: Discussionmentioning
confidence: 99%
“…We observed temporal changes in these subpopulations over the course of the inflammatory response that indicate a close interaction with mesenchymal progenitor cells leading to aberrant healing. While immune modulating therapies have become a mainstay in cancer therapies, they have failed to translate to diseases of nononcogenic aberrant cell fate [36][37][38][39] . Here, we have validated a therapeutic approach that modulates the macrophage phenotype to prevent aberrant musculoskeletal regeneration in a model of HO.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of sunitinib with immunotherapeutic approaches is somewhat controversial. Sunitinib has been shown to enhance intratumoral infiltation of CD8+ T-cells in combination with a CD40 agonist, a member of the tumor necrosis factor (TNF) superfamily [48] and to suppress immune regulatory cells in combination with celecoxib [49]. On the contrary, sunitinib has been reported to inhibit anti-tumor vaccination by decreasing antigen presenting cells [50] and to impair proliferation and function of phytohemagglutinin (PHA) stimulated human T-cells [51], in agreement with our results showing a decrease in tumor infiltrating T-cells following sunitinib-PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (42) identified that the combination of sunitinib with celecoxib resulted in a longer time to tumor progression compared with treatment with either agent alone or compared with untreated control animals in four models. Zhao et al (11) have also revealed that combination therapy consisting of sunitinib and celecoxib exerts improved curative effects against RCC compared with any monotherapy and identified that immunoregulatory cells may be involved in this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Celecoxib, a selective COX-2 inhibitor, is a clinically effective drug as it can inhibit COX enzymes and consequently prevent, inhibit or abrogate the effects of prostaglandins (10). Previous studies have reported the antitumor effect of celecoxib against RCC (11,12).…”
Section: Introductionmentioning
confidence: 99%